Estrategias metodológicas en el área de lengua y literatura para estudiantes con TDAH de 4to año de básica de la Unidad Educativa Adolfo María Astudillo cantón Babahoyo, Provincia de Los Ríos 2022 - Ramos López, Odalis Edith (2022)
The present research work was carried out through the problem that arises in the classroom of students with Attention Deficit Hyperactivity Disorder (ADHD) of the 4th year of basic education of the "Adolfo María Astudillo" Educational Unit, located in the Babahoyo-Los Ríos Cantón. As it is knowledge, the most feasible way to reach the student is through methodological strategies, since it is a procedure that offers an easy way to improve the process of acquiring knowledge. It is due that when applied it is according to the particularities and characteristics of the student; that increase meaningful learning with student skills and understanding. This research is of a documentary nature, with the objective of determining the importance of the use of methodological strategies in the area of language and literature, generating in students the due interest in improving and increasing their teaching-learning process. The reason for the selection of these methodological strategies for the development of students was developed for easy use by teachers in order to apply these methods with students with ADHD to maintain a high level of attention and reduce the hyperactivity.